2020
DOI: 10.1186/s43055-019-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlative study between ADC value and grading of invasive breast cancer

Abstract: Background Studying breast carcinoma is of great importance as it is the commonest female malignancy. Accurate preoperative assessment of disease characteristics and prognosis would be of great help in the diagnosis and treatment planning of breast cancer. The aim of this study was to evaluate the role of the apparent diffusion coefficient (ADC) value in detecting the grading of invasive breast carcinoma prior to management. Results There was a significant difference between the mean ADC value of tumors of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We considered high grades to be grade III and low grades to be grades I and II. There was no significant difference between grades II and III using ADC in an earlier study 55 . Similar results were found in our analysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We considered high grades to be grade III and low grades to be grades I and II. There was no significant difference between grades II and III using ADC in an earlier study 55 . Similar results were found in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…In the characterization of low‐ versus high‐grade tumors, the SVM classifier using the WBFS method displayed 0.94 sensitivity, 0.80 specificity, an F1 score of 0.92, and 0.24 RMSE with 10‐fold CV over 10 repetitions in our cohort. Several studies have reported on the relationship between ADC value and the histological grade of breast cancer, with varying results 52–55 . This variation may be attributable to the discrepancy in the sample size and the MRI technique, especially the use of different b‐values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ADC maps, tissues with high cellularity showed lower ADC values [20,21]. Recent literature has demonstrated an inverse correlation between ADC values and histological grade of the tumor, proving its usefulness in identifying high-grade invasive breast cancer prior to the surgery [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant difference between grade II and III tumors (p ¼ 0.979). 5 We thank the authors for showing the potential value of utilizing ADC maps with specific cut-off values as an additional useful predictive marker for malignant breast lesions, as well as a potentially helpful tool for tumor grading.…”
mentioning
confidence: 99%